2020
DOI: 10.32479/ijefi.9959
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intellectual Capital Efficiency on Bank Risks: Empirical Evidence From the Saudi Banking Industry

Abstract: The main purpose of conducting this research is to investigate the impact of intellectual capital efficiency (ICE) and its components -human capital efficiency (HCE) and structural capital efficiency (SCE) -on bank credit and insolvency risks in the Saudi banking industry. To assess such a relationship, value added intellectual coefficient model (VAIC) along with a couple of panel data techniques were utilized by using quarterly observations spanning from the first quarter of 2009 to the fourth quarter of 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…The result of the study is very much important for the bank management to think about the investment in IC, as it indicates that there is an increase of bank's risk with the increase in investment IC. The result of the study agreed with the study Zheng et al, (2018) and disagreed with the study of Alrashidi and Alarfaj, (2020). The results of the study slightly nuance with resource-based theory that state that firms' strategic valuable resources help in improving effectiveness and neutralize the threats Barney (1991).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The result of the study is very much important for the bank management to think about the investment in IC, as it indicates that there is an increase of bank's risk with the increase in investment IC. The result of the study agreed with the study Zheng et al, (2018) and disagreed with the study of Alrashidi and Alarfaj, (2020). The results of the study slightly nuance with resource-based theory that state that firms' strategic valuable resources help in improving effectiveness and neutralize the threats Barney (1991).…”
Section: Discussionsupporting
confidence: 60%
“…So, in this study we can expect a negative correlation, but different outcome also found in the past literature regarding the relationship. Several prior studies, such as, Ghosh and Maji (2014); Zheng et al, (2018); Nawaz et al (2019); Innayah et al (2020); Alrashidi and Alarfaj, (2020), Innayah et al, (2020) found negative association between IC efficiency. But opposite result also found in study of Guimon (2005); Nawaz et al, (2019); Sun and Chang (2011) claimed that IC could have positive effect on credit risk as they help in evaluating the organizational competitiveness and provide fine image of firm's management team.…”
Section: Relationship Between Ice and Riskmentioning
confidence: 85%
“…Ref. [13] supports this, noting the importance of intellectual capital in managing risks in the Saudi banking industry. This aspect is particularly vital as banks face increasingly volatile financial markets.…”
Section: The Impact Of Intellectual Capital On Sustainable Bank Perfo...mentioning
confidence: 84%
“…While leverage can amplify returns by increasing the resources available for investment, it also elevates financial risk. Empirical research supports a generally positive, though complex, relationship between leverage and bank profitability, indicating that careful leverage management is essential to avoid excessive risk (Alshadadi & Deshmukh, 2023;Alrashidi & Alarfaj, 2020).…”
Section: Internal Control Variables Macroeconomic Indicators and Covi...mentioning
confidence: 99%